Management of Refractory Malignancy-Associated Hemophagocytic Lymphohistiocytosis in Adolescent Patients: A Case Series of Novel Therapeutics and Treatment Challenges - Meha Krishnareddigari; Kenny Vo; Arun Panigrahi (Hematology Reports)
Background: Hemophagocytic lymphohistiocytosis (HLH) is a potentially fatal syndrome of immune dysregulation with primary (genetic) and secondary (acquired) forms, including malignancy-associated HLH (m-HLH). The condition often presents significant diagnostic and therapeutic challenges due to overlapping symptoms with underlying malignancies and the absence of standardized guidelines for refractory cases. The established standard of care is dexamethasone and etoposide, but no guidelines exist for refractory HLH or cases triggered by malignancy. Case presentations: This case series describes three adolescent patients with m-HLH, focusing on complexities in diagnosis, treatment regimens, and toxicity management. While dexamethasone and etoposide remain a standard of care, their efficacy in refractory cases is limited. We highlight the novel use of targeted therapies, including emapalumab, an interferon-gamma inhibitor, and ruxolitinib, a JAK1/2 inhibitor, which showed potential in modulating immune hyperactivation. Conclusions: Our findings emphasize the need for individualized treatment approaches in adolescent m-HLH and importance of further research to establish evidence-based therapeutic guidelines for refractory cases.